Solution Properties of Polysaccharides from Anacardium occidentale - Zakaria, Mat; Ab Rahman, Zainiah; Nik Mahmood, Nik Noor Aini (Universiti Putra Malaysia Press, 1997)
The viscosities of fractions of polysaccharide obtained from Anacardium occidentale dissolved in aqueous solutions were measured. Investigation by potentiometric titration and determination of common metal ion contents in the gum indicated that the solubility and viscosity differences of the fractions may be attributable to the difference in the degree of acylation and the content of the divalent cations present in the fractions. The fractions with higher degrees of acylation form a gel, but when partially deacylated disperse in water to form a stable gel dispersion. The higher viscosity exhibited by the soluble fraction is attributable to the higher content of divalent cations.